Design of an integrated biomass gasification and proton exchange membrane fuel cell system under self-sustainable conditions: Process modification and heat-exchanger network synthesis. (5th January 2017) - Chutichai, Bhawasut; Im-orb, Karittha; Alvfors, Per; Arpornwichanop, Amornchai
Abstract: The design and analysis of an integrated biomass gasification and PEMFC system to generate heat and power demand for residential applications are presented in this study. Two biomass gasification configurations using sawdust as a feedstock are considered: air–steam biomass gasification (AS-BG-PEMFC) and steam-only biomass gasification (SO-BG-PEMFC). The biomass processing consists of a biomass gasification which is used to produce H2 -rich gas (syngas), followed by high- and low-temperature shift reactors and a preferential oxidation reactor. Pinch analysis is performed to evaluate and design a heat-exchanger network in the two biomass gasification systems. The remaining useful heat is recovered and employed for a reactant preparation step and for a heating utility system in a household. The simulation results indicate that the SO-BG-PEMFC generates syngas with a greater H2 content than the AS-BG-PEMFC, resulting in higher fuel processor and electric efficiencies. However, the AS-BG-PEMFC provides a higher thermal efficiency because a high-temperature gaseous product is obtained, and more energy is thereby recovered to the system. The total heat and power efficiencies of the AS-BG-PEMFC and the SO-BG-PEMFC are 83% and 70%, respectively. The Sankey diagram of energy flows reveals that the performance improvement depends entirely on the utilization of useful energy in the exhaust gas. Highlights: An integrated biomass gasification and PEMFC system is studied. Design of the PEMFC system is proposed based on a combined heat and power approach. The PEMFC system operated under self-sustainable conditions is considered. Pinch technology is employed for heat exchanger network design. Energy analysis of the designed PEMFC system is performed.